Implementation of an Automata Mechanism for a Self-Organizing Swarm of Drones Platform - Atashyan, Agit F.; Lazyan, Artyom A.; Hayrapetyan, Davit V.; Poghosyan, Vahagn S. (Mathematical Problems of Computer Science, 2025)
Drone technology has enabled major advancements in autonomous systems, particularly in swarm robotics. This paper presents a novel automation technique aimed at enhancing the efficiency, adaptability, and robustness of self-organizing drone swarms. The system uses decentralized control algorithms and robust communication protocols to enable real-time adaptive learning and decision-making among drones. Each drone acts as an autonomous agent, adjusting its behavior based on environmental inputs and interactions with other drones. A hybrid communication model blending peer-to-peer and cluster-based protocols ensures effective information sharing and coordination. To build a scalable and resilient architecture, multi-agent systems theory is integrated with advanced self-organizing strategies. Extensive modeling and realworld testing evaluated the systems performance in complex scenarios such as disaster response, environmental monitoring, and surveillance. Results demonstrate significant improvements in swarm efficiency, resilience to failures, and adaptability to dynamic environments. The incorporation of adaptive learning algorithms further optimized task allocation and execution in real time. This work represents a substantial advancement in autonomous aerial robotics, offering a comprehensive framework for deploying intelligent, self-organizing drone swarms and highlighting the transformative potential of automata-based approaches in future autonomous systems.